2018
DOI: 10.1073/pnas.1721604115
|View full text |Cite
|
Sign up to set email alerts
|

Converting Escherichia coli into an archaebacterium with a hybrid heterochiral membrane

Abstract: SignificanceEscherichia coli has been engineered toward an archaebacterium with an unprecedented high level of archaeal ether phospholipids. The obtained cells stably maintain a mixed heterochiral membrane. This finding challenges theories that assume that intrinsic instability of mixed membranes led to the “lipid divide” and the subsequent differentiation of bacteria and archaea. Furthermore, this study paves the way for future membrane engineering of industrial production organisms with improved robustness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 48 publications
(61 reference statements)
3
62
1
1
Order By: Relevance
“…Further, and building on previous results showing that the archaeal lipid pathway can be successfully expressed in recombinant bacteria, an Escherichia coli ( E. coli ) strain was recently engineered to contain the full set of archaeal lipid‐making genes . Not only did the chimeric bacteria successfully synthesize the archaeal lipids, but the heterotypic membranes actually proved advantageous under a number of environmental‐stress conditions.…”
Section: Mixed Archaeal–bacterial Lipid Membranes Are Viable In the Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, and building on previous results showing that the archaeal lipid pathway can be successfully expressed in recombinant bacteria, an Escherichia coli ( E. coli ) strain was recently engineered to contain the full set of archaeal lipid‐making genes . Not only did the chimeric bacteria successfully synthesize the archaeal lipids, but the heterotypic membranes actually proved advantageous under a number of environmental‐stress conditions.…”
Section: Mixed Archaeal–bacterial Lipid Membranes Are Viable In the Lmentioning
confidence: 99%
“…Conversely, membranes built with archaeal‐like lipids remain impermeable and liquid‐crystalline at the entire range of temperatures of life . As results from the laboratory suggest, such an advantage provided by archaeal lipids may suffice as an explanation for their presence in some bacteria (Figure A).…”
Section: Membrane Proteins As Drivers Of the Lipid Dividementioning
confidence: 99%
See 1 more Smart Citation
“…These seem to be of (mitochondrial) endosymbiont origin as well. [ 45 ] One also has to consider that, though mixing of the two membrane types turns out to be easily feasible, [ 46 ] we do not know whether endocytosis with archaeal membranes is easy as well. In light of their analyses, Dey et al.…”
Section: Predator/parasite Models Of Eukaryogenesis Can Be Challengedmentioning
confidence: 99%
“…It has also been suggested that LUCA may have had a heterochiral membrane (Wächtershäuser 2003), with later independent transitions to homochirality in Bacteria and Archaea, driven by increased membrane stability. However, the available experimental evidence -including the recent engineering of an Escherichia coli cell with a heterochiral membrane (Caforio et al 2018) -suggests that homochiral membranes are not necessarily more stable than heterochiral ones (Fan et al 1995;Shimada and Yamagishi 2011;Caforio et al 2018), requiring some other explanation for the loss of ancestral heterochirality.…”
Section: Introductionmentioning
confidence: 99%